DEVELOPMENT OF THE ABILITY OF SENIOR SCHOOL PUPILS TO COOPERATE IN THE CONTEXT OF FORMING LIFE SUCCESSFULNESS - Нечерда, Валерія (SWorldJournal, 2025)
The author outlined the main features of cooperation, noted the necessity for the ability to cooperate to form the life successfulness of a modern senior school pupil, and clarifies the concept of "pupil’s ability to cooperate". The research considered t